Enseigner-apprendre l'orthographe, des interactions langagières pour articuler gestes professionnels et gestes d'étude - Martine Champagne-Vergez; Maryse Rebière; Martine Jaubert (Nantes Université, 2020)
The article focuses on the teaching and learning of the French language system, a particularly critical subject, to the extent that the distinction between the language object to be learned and the language means of learning can be a source of misunderstanding between the teacher and the pupils. In this vast and complex system, we focus on the spelling that allows us to approach the whole because it is very strongly articulated with grammatical dimensions. How do language interactions inform us about how the teacher sees his or her action and how his or her students behave according to their expectations: Our hypotheses take two paths: the teacher's consideration of the teaching situation and the gradual involvement of pupils and the progressive involvement of pupils in learning language gestures through changes in enunciative positioning as a result of teachers' didactic language gestures. To answer this problem, we rely on a corpus collected in elementary school classes, from the CE1 (7 years) to the CE2 (8 years) in contrasting socio-economic environments. We study the language interactions and analyse what is common and what is different between the devices, trying to follow the thread of a genesis of knowledge, between epilinguistic and metalinguistic verbalizations, in order to capture linguistic phenomena at work and in particular scenarios and their appropriation.